Community versus institutionalised care for people with severe mental illness in five countries in Southeast Europe: pooled analysis of five randomised trials - Shields-Zeeman, Laura; Smit, Filip; Wijnen, Ben; Roth, Catharina; Wensing, Michel; Petrea, Ionela; Bolinski, Felix; Bajraktarov, Stojan; Dedovic, Jovo; Keet, René; Kuzman, Martina Rojnic; Nakov, Vladimir; et al. (BMJ global health, 2025)
Background The RECOVER-E project implemented community-based mental healthcare (CMH) oriented at functional recovery in people with schizophrenia, bipolar and severe major depressive disorder in five countries: Bulgaria, Croatia, Montenegro, North Macedonia and Romania, with the aim to shift care from institutions to communities.Objective To evaluate the effectiveness of CMH under real-world circumstances across various healthcare ecologies and contexts.Methods A randomised comparison of CMH versus treatment as usual (TAU) based on pooled data from all five RECOVER-E trials (N=931). Outcomes were personal and social role functioning (WHO Disability Assessment Schedule, WHODAS 2.0) and health-related quality of life (EuroQoL-5 Dimensions-3 Levels) at baseline, 12 and 18 months postbaseline. Intention-to-treat analysis was conducted with mixed modelling and a sensitivity analysis adjusted for the impact of COVID-19 on healthcare delivery and outcomes.Findings At 18-month follow-up, CMH had a 4.55 lower WHODAS disability score than TAU, which was significant (b=−4.55, SE=1.21, z=−3.75, p<0.001), and improved quality of life by 0.07 utility (b=0.07, SE=0.014, z=4.56, p<0.001) equivalent to an additional 25 days in full health. Similar effects were observed in each of the five countries and for all WHODAS subdomains (cognition, mobility, self-care, getting along with people, life activities, participation). Sensitivity analyses adjusting for the confounding effect of COVID-19 showed similar effects.Clinical implications Recovery-oriented CMH for people with severe mental illness was effective in improving functioning and quality of life for people with schizophrenia, bipolar disorder and severe depression in five South-Eastern European countries and could be implemented across different health systems.Trial registration numbers Bulgaria: NCT03922425, Croatia: NCT03862209, Macedonia: NCT03892473, Montenegro: NCT03837340, Romania: NCT03884933.
Gesehen am 10.12.2025